URINARY RETENTION EFFECT IN THE INCREASED OF PSA EXPRESSION WITHIN PROSTATIC TISSUE - Djatisoesanto, Wahjoe; Soebadi, Doddy M; Sudiana, I Ketut (Indonesian Urological Association, 2015)
Objective: To determine whether the increased of PSA expression within prostatic tissue and subsequent systemic blood circulation in acute urinary retention cases of nonmalignant origin were caused by acute inflammation on the prostatic gland. Following this inflammation, PSA willincrease, producing byacinar epitelial cells in the gland and continue to capillary vessels before entering the blood circulation. Material & method: Thirty male Rattus Norvegicus were randomly allocated into 3 groups. A control group underwent urethral manipulation, treatment-1 group and -2 group underwent proximal urethral ligation. Prostatectomy was performed after 24 hours in the control and treatment-1 group. Ligation was removed after 24 hours in treatment-2 group, and prostatectomy performed after 4x24 hours. Each prostate specimen was examined for PSA expression by immunohistochemistry methods in the prostatic gland. Statistical analysis of study data was analyzed by descriptive statistics and performed ANOVA with level of significance α = 0.01.Results: Study results showed an increase PSA expression significantly after urinary retention and returned to normal values four days later after relief of retention.Conclusion: Urinary retention caused acute inflammation on the prostatic gland and increased PSA expression within prostatic tissue. Entry of PSA into stroma and subsequent systemic blood circulation occur through significant increase in PSA production by acinar epithelial cells.